Human Capital Accumulation and Migration in a Peripheral EU Region: the Case of Basilicata - Nicola D. Coniglio; Francesco Prota (European Regional Science Association (ERSA), 2003)
The importance of human capital as a key source of value added, innovation and economic growth is widely acknowledged by both economists and policy-makers. Local governments can directly affect individuals' decision making by subsidising human capital formation. The ability of a regional system to generate human capital is crucial but it is not a sufficient condition leading to economic success. In this work we emphasise the importance of maintaining and attracting high-skilled individuals, and the challenge that migration flows pose on policymaking aimed at fostering human capital accumulation. Human capital does not always benefits the region where it was funded and the scope for the policy might vanish if the human capital formed locally is lost through migration, as emphasised by the “brain drain” literature. When agglomeration forces are at work, human capital migrates from where it is scarce to where it is abundant, rather than vice versa (Lucas 1988). This can result in migration widening the regional wage and income gap and lowering the standard of living in the peripheral location. Poor regions lose through migration their most valuable residents, the main source of innovation and productivity in a modern economy. This phenomenon contributes in explaining the persistent nature of regional economic imbalances. These consideration are highlighted through the analysis of a case study, the migration decision of a sample of highly educated and skilled individuals residing in a small peripheral Mezzogiorno region (Basilicata) which have benefited from a locally funded human capital investment policy. The regional policymakers, in recognition of the importance of human capital as a key ingredient for regional growth, have given generous subsidies since the beginning of the 90s to young graduates who wanted to attend a post-graduate course outside or inside the region. More than a thousand individuals have benefited from the policy in the last decade, and the target for the period 2000-2006 is to subsidise an additional two thousand individuals. A dataset was generated through a survey questionnaire which aims at directly asking people about their decision whether or not to move and the main factors influencing their decision. For each individual, we have collected data on background, experience and outcome of higher education, opinion on the quality of the course attended, job-search strategy after the course, and space-time career details from the first employment to the current employment status. The policy intervention under scrutiny and in particular the biased nature of the sample (highly skilled and educated individuals) makes the analysis a natural experiment for assessing the ability of the regional system in a peripheral EU region not only to generate human capital but also to maintain it. The focus of the paper is on the micro level migratory behaviour. In particular, we want to shed light on the following questions: (1) Who are the migrants; (2) What are the main factors influencing migration; (3) What is the resulting “geography” of the human capital generated? Is the human capital attracted toward core regions'
Keywords: 330